Carbapenem-Resistant Enterobacteriaceae Detection Practices in California: What Are We Missing?. (1st November 2017) - Humphries, Romney M; Hindler, Janet A; Epson, Erin; Horwich-Scholefield, Sam; Miller, Loren G; Mendez, Job; Martinez, Jeremias B; Sinkowitz, Jacob; Sinkowtiz, Darren; Hershey, Christina; Marquez, Patricia; Bhaurla, Sandeep; et al.
Abstract : Large-scale survey identified hospital laboratories (28%) do not use the Infectious Diseases Society of America and Clinical and Laboratory Standards Institute breakpoints for Enterobacteriaceae and isolates (19%) may be misclassified, impacting public health outbreak detection and clinical care of patients. Abstract: Background: The Clinical and Laboratory Standards Institute (CLSI) revised the carbapenem breakpoints for Enterobacteriaceae in 2010. The number of hospitals that adopted revised breakpoints and the clinical impact of delayed adoption has not been explored. Methods: We performed a cross-sectional, voluntary survey of microbiology laboratories from California acute care hospitals and long-term acute care hospitals (LTAC) to determine use of revised CLSI breakpoints. Carbapenem-resistant Enterobacteriaceae (CRE) clinical isolates from a single tertiary-care hospital from 2013 to 2017 were examined. All isolates with an elevated minimum inhibitory concentration (MIC; ≥2 µg/mL) to imipenem or meropenem were tested for the presence of carbapenemase genes by polymerase chain reaction (PCR). Results: We received responses from 128 laboratories that serve 264/393 (67%) of hospitals and LTACs. Current CLSI carbapenem breakpoints for Enterobacteriaceae were used by 92/128 (72%) laboratories. Among laboratories that used current breakpoints, time to implementation varied from 0 to 68 months (mean, 41 months; median, 55 months). Application of historical breakpoints to isolates with a carbapenemase gene detected by PCR resulted in susceptibility rates of 8.9%, 18.6%, and 18.6% to ertapenem, imipenem, and meropenem, respectively. By current breakpoints, <1% of these isolates were susceptible to ertapenem or imipenem and 2.6% to meropenem. Conclusion: Clinicians and epidemiologists should be aware that use of outdated MIC breakpoints for Enterobacteriaceae remains common and can result in reports of false susceptibility to carbapenems and missed identification of carbapenemase producers. This misclassification could have consequences for patient care and infection control efforts to address carbapenemase-producing Enterobacteriaceae .